IOT Based Indoor Lighting Performance of Led With Different Color Temperatures System Based on Human Activity - Angger Dwi Ardiatma; Benfano Soewito (Jurnal Syntax Admiration, 2023)
Numerous LED light brands are available on the market, each offering a variety of light colors, including warm white (2700 K), white (3000 K), cool white (5000 K), and daylight (6000 K). Each color of light produces heat in the form of different lights in the room. Living things have a physiological ability called circadian rhythm to adapt to changes in their environment due to rhythmic physiological influences on hormonal secretion, temperature, wake-sleep rhythm, glucose balance, and cell regulation cycles. Lighting sources should also be human-friendly, especially with regard to the increased hazards from shortwave emissions. Extended periods of exposure to white light that contains blue and/or violet wavelengths can suppress the production of melatonin, leading to higher secretion of female hormones. This, in turn, elevates the likelihood of developing breast cancer. This paper aims to design a lighting regulation system based on human activity and light color regulation with circadian rhythm for 24 hours a day. This system employs the Internet of Things (IoT) along with multiple sensor systems and WS2812B LEDs. By applying fuzzy logic, it generates outputs that effectively regulate the brightness and color of the lights. The research findings demonstrate that indoor lighting can be easily adapted by utilizing various sensors and fuzzy logic techniques to detect human activity. As a result, the intensity and color of the lights can be automatically adjusted based on human activity, and the IoT allows for remote control of the system.